2020
DOI: 10.1016/j.pvr.2020.100206
|View full text |Cite|
|
Sign up to set email alerts
|

CINtec PLUS and cobas HPV testing for triaging Canadian women referred to colposcopy with a history of low-grade squamous intraepithelial lesion: Baseline findings

Abstract: Objective and methods CINtec PLUS and cobas HPV tests were assessed for triaging women referred to colposcopy with a history of LSIL cytology. Both tests were performed at baseline using ThinPrep cervical specimens and biopsy confirmed cervical intraepithelial neoplasia grade 2 or worse (CIN2+) served as the clinical endpoint. Results In all ages, (19–76 years, n = 600), 44.3% (266/600) tested CINtec PLUS positive vs. 55.2% (331/600) HPV positive (p = 0.000). Based on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Age ranged from 19 to 76 years (median, 33.0), with 384 (64.2%) 30 years of age (median, 43.0). (In our baseline paper [ 16 ], the total number of patients with evaluable results was reported as 600. Upon final review, 2 patients were found not to have met study inclusion criteria and removed from our final analysis, resulting in 598 patients in the study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Age ranged from 19 to 76 years (median, 33.0), with 384 (64.2%) 30 years of age (median, 43.0). (In our baseline paper [ 16 ], the total number of patients with evaluable results was reported as 600. Upon final review, 2 patients were found not to have met study inclusion criteria and removed from our final analysis, resulting in 598 patients in the study.…”
Section: Resultsmentioning
confidence: 99%
“…For those with LSIL cytology, either direct referral to colposcopy or repeat cytology at 6-month intervals is recommended; for those having persistent atypical squamous cells of undetermined significance (ASCUS) or worse in repeat cytology, colposcopy is recommended [ 1 ]. In colposcopy clinics, all referred patients undergo cytology and colposcopic examination with biopsies of any lesions detected, and further follow-up clinical pathways depend on specific criteria as previously described [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations